Multiple Stepwise Gene Knockout Using CRISPR/Cas9 in Escherichia coli - König, Enrico (Bio-Protocol, 2018)

(untitled) (Bio Protoc)
With the recent implementation of the CRISPR/Cas9 technology as a standard tool for genome editing, laboratories all over the world are undergoing one of the biggest advancements in molecular biology since PCR. The key advantage of this method is its simplicity and universal applicability for species of any phylum. Of particular interest is the extensively studied Gram-negative bacterium Escherichia coli, as it is considered as the workhorse for both research and industrial purposes. Here, we present a simple, robust and effective protocol using the CRISPR/Cas9 system in combination with the λ Red machinery for gene knockout in E. coli. Crucial in our procedure is the use of a double-stranded donor DNA and a curing strategy for removal of the guide RNA encoding plasmid that allows starting a new mutation after only two working days. Our protocol allows multiple, stepwise gene knockout strains with high mutagenesis efficiencies applicable for high-throughput approaches.